Theoretical and experimental free vibration analysis of a beam-tendon system with an eccentrically placed tendon. (November 2019) - Ondra, V.; Titurus, B.
Abstract: Theoretical and experimental free vibration analysis of a beam-tendon system is presented in this paper. The system consists of a thin-walled cantilever beam with an open cross-section and a tip mass which is loaded by an eccentrically placed tendon. The novel beam-tendon system is modelled using a set of partial differential equations and numerical free vibration analysis is conducted using a boundary problem solver. The results are thoroughly validated using a bench-top experiment and a high-fidelity finite element model. The effect of the tendon location on the frequency-loading diagrams is systematically investigated for the first time. The results demonstrate that the location of the tendon significantly influences natural frequency shifts caused by the applied axial load and it is observed that some natural frequencies can even increase with the increasing compressive axial loading for certain locations of the tendon. In addition, veering between the beam-dominated and tendon-dominated modes is studied and the structural stability of the system is discussed. The paper concludes with suggestions of practical applications of a beam-tendon system with an eccentrically placed tendon. Highlights: A beam axially loaded by an eccentrically placed tendon is studied. A theoretical model of the beam-tendon system is validated using an FE model and experimentally. The effect of tendon location is shown to have significant effect on modal properties. Frequency loci veering between beam-dominated and tendon-dominated modes is observed. The impact of the tendon location on the structural stability is discussed.